Metabolic Evidence on Vintage Effect in Tea (Camellia sinensis L.) Plants - N. H. M. Rubel Mozumder; Kyeong Hwan Hwang; Min-Seuk Lee; Eun-Hee Kim; Young-Shick Hong (Applied Biological Chemistry, 2023)
Abstract Recent metabolomics studies have reported diverse metabolites of tea depending on tea (Camellia sinensis) cultivars, cultivation conditions and geographical location. However, these studies were limited the effects of these conditions on metabolome of tea leaves in a single year. We explored the year-to-year variations in leaf metabolome of two tea (C. sinensis) cultivars over a period of five successive years from 2015 to 2019 to determine vintage tea products, such as in grapes or wines, and showed a clear metabolic differentiations of fresh tea leaves. Also, the best conditions of climate were suggested through an association of rainfall and sun-expose time with the metabolism of theanine in taste- or flavor-rich tea cultivar and of catechin compounds in EGCG3″Me-rich tea cultivar, thereby providing the potential vintage tea tailored to the cultivar. Since vintage wine is derived from grapes grown in a year under good climatic conditions, which provides high quality of wine in the best year, the current result highlights important information relevant to tea metabolome associated with climatic conditions in a specific year and the manufacture of vintage tea with unique quality. Graphical Abstract